CROSS-CULTURAL VALIDATION AND RELIABILITY OF THE MALAY VERSION OF THE DEMENTIA PUBLIC STIGMA SCALE (DEPSS-M) AMONG MALAYSIAN ADULTS - Fadzil, Siti Sarah; Nik Farid, Nik Daliana; Yahya, ’Abqariyah; Kamaruzzaman, Shahrul Bahyah; Anuar, Farah Nurulhuda (Malaysian Journal of Public Health Medicine, 2025)
The prevalence of dementia is predicted to increase in the following decades, but dementia-related stigma continues to exist in the current society. The Dementia Public Stigma Scale (DePSS) was developed to assess this problem. However, it has not been translated and validated among the general public in Malaysia. To better understand the public stigma on dementia within the Malaysian context, we cross-culturally adapt the English version of DePSS into the Malay language. A study was conducted among Malaysian adults attending the Ministry of Health (MOH) primary care health services in Selangor, Malaysia, from May to November 2024. A forward and backward translation was performed, followed by content validation by ten local experts. A total of 35 participants were recruited for the pilot study and test-retest reliability. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were subsequently conducted on 491 participants from diverse backgrounds. The original 16-item with a 5- factor model of DePSS was reduced to 13 items with a 4- factor model in the Malay version of DePSS (DePSS-M). The revised DePSS-M demonstrated good factor loadings (0.60-0.98) with an excellent model fit on CFA ( RMSEA=0.07, GFI=0.93, TLI=0.91, CFI=0.94). The DePSS-M also displayed sufficient convergent (AVE less than 0.5) and discriminant validity ( less than 0.85) across all constructs. The reliability assessment revealed good internal consistency with acceptable Cronbach’s alpha (0.78-0.85) and composite reliability (CR) (0.78-0.86). In conclusion, the DePSS-M is a valid and reliable tool that can be used to assess public stigma on dementia in Malaysia. It can also be used to inform local dementia-related policies and direct future stigma reduction strategies.